Bullying entre escolares do ensino médio : o fenômeno em escolas do município de Sobral – Ceará - Moraes, Késia Marques (2012)
Bullying is the name used for a range of aggressive behaviors, delivered in an intentional and repetitive way, without an apparent motivating stimulus. It can be variously classified as: verbal, physical and material, psychological and moral, sexual and virtual or ciberbullying. The study objectives were to analyze the situation of bullying among students of the Public Schools in Sobral - CE, to describe the socioeconomic, cultural and behavioral of the students, to identify situations in which students find themselves as victims, aggressors or observers and investigate the confrontation mechanisms of the victims against the bullying. This is a cross-sectional study conducted from September to December 2011 in thirteen state schools in the city of Sobral – CE with 369 students. To identify differences between groups of students who were victims, witnesses and aggressors were conducted Pearson’s chi-square test being used p value less than 0.05. The data were analyzed in Excel and SPSS 15. The results show that 18.4% of students consider themselves victims of aggression, the witnesses are configured in 44.4% and 9.5% are classified as aggressors. As to the types of aggression, there is the verb form, identified by 75% of students surveyed, followed by psychological and physical form. With regard to age, the older, lesser is the chance of the student becoming victim of aggression (p <0.05). By associating the family arrangement with the presence or absence of aggression (p <0.05), those whose parents are separated / divorced are more likely to be abused than children of married parents. When it comes to variety and age, students in third grade and older witness fewer episodes of aggression (p <0.05). About the event location, the classroom is configured as primary site, followed by the space time interval. But, as regards the number and age, students of 3rd year and older witness fewer episodes of aggression (p <0.05). This study may contribute to help parents, educators, students, health professionals and managers in facing this problem in search of an acting education with effective public policies.